Islam itu no galau : Ketahui rumusnya, galaupun minggat / Ahfa Waid ; editor, Sekar Bella ; ilustrator, Triastanto S. - AHFA WAID, 1994; Sekar Bella; Tristianto S. (Diva Press, 2014)
229 hlm. : ilus. ; 19 cm